Disparities in Long-Acting Reversible Contraceptive Utilization among Married Women in Ethiopia: Findings of the Ethiopian Demographic and Health Survey - Haile, Biniyam Tadesse (Int J Reprod Med, 2020)
BACKGROUND: Long-acting contraceptive methods, subdermal implants, and intrauterine devices are reliable, safe, and cost-effective family planning methods. However, these methods are not widely used in Ethiopia despite government effort to increase access. The study is aimed at assessing the rate of utilization of long-acting contraceptive methods among married women and associated factors. METHOD: We analyzed the 2016 Ethiopian Demographic and Health Survey dataset. A total of 2045 married women of reproductive age group, who were using any modern contraceptive method at the time of the survey, were included in the study. Descriptive statistics were computed to characterize the study participants. Bivariate and multivariable logistic regression analyses were performed to identify associated factors, reporting odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULT: The multivariable analyses showed that women educational status, parity, religion, previous history of abortion, desire for more child, and region where the respondents reside were significantly the factors that determine the utilization of long-acting contraceptive. There is a significant regional disparity in long-acting contraceptive utilization. Compared to women residing in Tigray region, those who live in other regions (Afar-Somali, Oromia, Amhara, Benishangul Gumz-Gambela, and Southern Nations Nationalities and People) have low likelihood of using long-acting contraceptive methods. CONCLUSION: Utilization of long-acting family planning method is low in Ethiopia. There is a significant regional disparity in utilizing these methods. Policy makers should promote culture-sensitive and tailored interventions to improve the utilization of long-acting family planning methods.